Мовні маркери стратегії маніпуляції в заголовках українського, польського і російського медіадискурсу - Natalia Kondratenko (Acta Universitatis Wratislaviensis. Slavica Wratislaviensia)
The article analyzes headlines and headline complexes of electronic media publications of Ukraine, Poland and Russia. The focus is on media texts for 2022 dedicated to the events of the war in Ukraine. The purpose of the study is to determine the main linguistic means of implementing a manipulative strategy of interaction with potential addressees in the modern media discourse in a comparative aspect. The specifics of manipulative influence and manipulation are defined, and the linguopragmatic parameters of the analysis of media texts are characterized. The researcher focused on the communicative strategy of manipulation. This resulted in the representation of the definition of manipulation as a destructive phenomenon in communication. Graphical, lexical and grammatical means of implementing a manipulative strategy are analyzed in the headlines of media texts. The main attention is paid to semantic aspects. The main concepts of the implementation of the manipulation strategy in media headlines have been determined. The analysis was carried out in a comparative aspect. I compared the headlines in the media publications of Ukraine, Poland and Russia. The dominance of manipulative strategy in Russian media texts and suggestive influence in Ukrainian and Polish media discourse is analyzed. The typology of language means of implementing the strategy of manipulation in media headlines is represented.